Revisiting Entrepreneurial Opportunity Recognition: An Integrative Systematic Review of Human Capita, Cognition, and Capabilities - Muskinta Muskinta; Yunia Wardi; Sandi Heri; Susi Evanita (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study aims to systematically examine the relationship between entrepreneurial human capital and opportunity recognition by integrating cognitive and capability based perspectives. Although prior research highlights the importance of human capital in entrepreneurship, the mechanisms linking it to opportunity recognition remain theoretically fragmented. To address this gap, this study employs a systematic literature review using the PRISMA protocol and analyzes peer reviewed articles from leading entrepreneurship and management journals.The findings indicate that entrepreneurial human capital serves as a foundational resource that enhances opportunity recognition through cognitive mechanisms, including entrepreneurial alertness, information processing, and opportunity perception. In addition, entrepreneurial capabilities such as knowledge integration capability, learning capability, and digital capability play a crucial role in transforming cognitive insights into opportunity discovery and exploitation. The review also shows that opportunity recognition increasingly occurs within digitally enabled entrepreneurial ecosystems. This study contributes by proposing an integrative framework that connects human capital, cognition, and entrepreneurial capabilities, positioning opportunity recognition as a dynamic and multilayered process. It enriches entrepreneurship literature by clarifying the mediating role of cognition and the enabling role of capabilities, while offering implications for education and policy development.